Culturally appropriate communication in Malaysia:budi bahasa as warranty component in Malaysian discourse - Ramli, Romlah (Routlege Taylor & Francis Group, 2013)
This paper discusses the Malaysian cultural appropriateness (CA), budi bahasa in communication. CA is a root anchoring Malaysian life and, indeed, all things Malaysian.Society inculcates the norms and taboos with clear-cut identification of the dos and don'ts in relational communication among (and between) Malaysians.Although Malaysians may practice different religious rituals or hold different ideologies, they still pay attention to being appropriate and polite in communication to respect each other's differences, a vital concern for those living in this multicultural country.In no small measure, budi (virtue/politeness) helps govern the rules of communication, but the term is nuanced, carrying with it multiple meanings derived from the cultural context. Traditionally, respect, care for other people's emotion, politeness and language use are among the criteria measuring a budi bahasa (man of culture).But, there are other measures as well. Budi bahasa (man of culture) is incorporated in the principles articulated in the Rukunegara.